Quality of life, Burnout and health indicators in nurses who work in rotating shifts - Vásquez-Yañez, José; Guzmán-Muñoz, Eduardo (Universidad y Salud, 2021)
Introduction: Rotating shift work has the potential to disrupt family and social life and can cause chronic fatigue, drowsiness, and somatic symptoms associated with circadian rhythm disorders. Objective: To compare quality of life, work stress, and health indicators in nursing professionals who work rotating and daytime shifts. Materials and methods: A descriptive cross-sectional study of observational design was conducted with 24 participants, who were divided into 2 groups according to type of work system that they performed: daytime or rotating shifts. The SF36 and Burnout questionnaires were applied and some health indicators were assessed. Results: Compared to nurses who work during daytime hours, those who work rotating shifts had a lower quality of life in the emotional role dimension (p=0.039), greater emotional fatigue (p=0.046), lower feelings of personal fulfillment at work (p=0.022), lower levels of basal insulin (p=0.005), lower HOMA-IR index value (p=0.007), and a higher amount of METs (Metabolic equivalents of task) spent weekly (p=0.041). Conclusions: Nurses who work rotating shifts show a lower quality of life and higher levels of physical activity and work stress than those who work during only daytime hours.